The “Granular and Quotidian, Dispersed and Tentacular”: Critical Reflections on CJLS Special Issue 35(2) – On the Margins of Trans Legal Change - Calder, Gillian (feminists@law, 2022)
Transgender and non-binary communities are facing shifting challenges on many fronts. The volume at the heart of this review essay is comprised of a collection of articles, sprung from a conference in Canada in May of 2019. They sit next to each other in conversation, creating an opportunity to broaden questions of the connections and dissonances between trans legal studies and other areas of critical legal inquiry. As argued by one of the authors, Samuel Singer, “Telling some of trans people’s legal stories also helps render visible the trans legal subject, which, albeit constituted within the narrative constraints of the legal system, brings us closer to centring trans people as legal actors.” Paying attention to the diverse stories of trans peoples, many of whom are living in the margins of Canadian society, shines an inclusive light on the plurality of their issues, stories, and lived experiences.